Regulation of energy balance by leptin as an adiposity signal and modulator of the reward system - Roshanak Asgari; Maria Caceres-Valdiviezo; Sally Wu; Laurie Hamel; Bailey E. Humber; Sri Mahavir Agarwal; Paul J. Fletcher; Stephanie Fulton; Margaret K. Hahn; Sandra Pereira (Molecular Metabolism)
Background: Leptin is an adipose tissue-derived hormone that plays a crucial role in body weight, appetite, and behaviour regulation. Leptin controls energy balance as an indicator of adiposity levels and as a modulator of the reward system, which is associated with liking palatable foods. Obesity is characterized by expanded adipose tissue mass and consequently, elevated concentrations of leptin in blood. Leptin's therapeutic potential for most forms of obesity is hampered by leptin resistance and a narrow dose–response window. Scope of Review: This review describes the current knowledge of the brain regions and intracellular pathways through which leptin promotes negative energy balance and restrains neural circuits affecting food reward. We also describe mechanisms that hinder these biological responses in obesity and highlight potential therapeutic interventions. Major Conclusions: Additional research is necessary to understand how pathways engaged by leptin in different brain regions are interconnected in the control of energy balance.